Implementation of Management Control System Towards Financial Risks in Business Chicken Farming in Pinrang District - Arfianty; Deasy Soraya A Aminartha; Nirwana Sampara; Sudirman (www.amertainstitute.com, 2025)
This study aims to analyze the implementation of management control systems in managing financial risks in Aslan Abbas' broiler chicken farming business in Pinrang Regency. The method used is qualitative research with interview techniques to obtain in-depth data related to planning, decision making, and financial risk management. The results of the study indicate that the implemented management control system has been running in a structured manner through detailed recording of capital, DOC purchases, feed, chicken mortality rates, and periodic evaluations. Risk management strategies include stabilizing operational costs by purchasing feed in large quantities when prices are low, collaborating with partners to maintain feed quality, and routine vaccination to reduce chicken mortality rates. Fluctuations in net profit in the last five periods were influenced by external factors such as feed prices and chicken mortality rates, but anticipatory strategies such as adjusting the number of DOCs and setting aside reserve funds managed to minimize the negative impacts. The implications of this study indicate that the implementation of an effective management control system can improve operational efficiency, maintain business stability, and support the sustainability of broiler chicken farming businesses in facing financial and market challenges.